ANALISA HUBUNGAN ANTARA INTELLECTUAL CAPITAL TERHADAP ORGANIZATIONAL LEARNING DALAM MENINGKATKAN FINANCIAL PERFORMANCE PADA INDUSTRI PERHOTELAN BINTANG 3, 4 DAN 5 DI JAWA TIMUR - Michella Hartono (Business Accounting Review, 2016)
This study aimed to examine the direct and significant affect of intellectual capital to organizational learning; organizational learning to financial performance; and intellectual capital to financial performance in the 3, 4 dan 5 stars hotels in East Java. This study also examined the indirect and significant relationship of intellectual capital to financial performance through organizational learning as intervening variable in the 3, 4 dan 5 stars hotels in East Java. This study used a quantitative approach, and the data were obtained through distributing questionnaires to 3, 4 dan 5 stars hotels in East Java and processed by using smart PLS software. Respondents in this research were accounting, finance, marketing staf, supervisor, manager and chief executive in the 3, 4 dan 5 stars hotels in East Java. This study showed that there was a positive and significant relationship of intellectual capital to organizational learning; organizational learning to financial performance; and intellectual capital to financial performance in the 3, 4 dan 5 stars hotels in East Java. But, organizational learning was inadequate as an intervening variable between intellectual capital and financial performance because the direct relationship between intellectual capital and financial performance gave greater affect than if it was through organizational learning.